Rectal Diazepam Solution Is as Good as Rectal Administration of Intravenous Diazepam in the First-aid Cessation of Seizures in Children With Intractable Epilepsy - Lin-Mei Chiang; Huei-Shyong Wang; Hsin-Hsien Shen; Shin-Tang Deng; Chi-Hao Tseng; Yu-In Chen; Ming-Liang Chou; Po-Cheng Hung; Kuang-Lin Lin (Elsevier, 2011)
Acute seizures are readily recognizable episodes requiring urgent treatment. This study was conducted to compare the efficacy and safety of suppository use of rectal diazepam solution [Stesolid rectal tube (SRT), Alpharma, Inc., Lierskogen, Norway] with those of intravenous diazepam (IVD), Li Ta Pharma Co, Ltd., Taichung, Taiwan for control of acute seizures in children with intractable epilepsy. Methods: Subjects were patients, aged 1-18 years, with intractable epilepsy under at least three kinds of antiepileptic treatments. Caregivers were trained to rectally administer SRT or IVD (dosage varying from 0.2 to 0.5 mg per kilogram of body weight) and to monitor respiration condition, seizure severity, and adverse drug effects. Results: Among the 24 subjects, 9 males and 15 females, treated for a period of 3 months, the ages ranged from 2 to 18 years, with a mean of 9.1 years. Seizure types were generalized tonic and/or clonic. Seizure frequency varied from once per week to 20 times per day. Twenty-one (87.5%) of them had mental retardation and/or developmental delay, and 103 of the 127 (81.1%) IVD administrations and 90 of the 103 (87.3%) SRT administrations resulted in rapid cessation of seizures within 10 minutes. Each first dose failed to control seizures in 24 and 13 episodes, respectively. A second dose of IVD achieved cessation of seizure in 21 of the 24 episodes and a second dose of SRT in 12 of the 13 episodes within another 10 minutes. Four episodes (3 with rectal IVD and 1 with SRT) of prolonged seizure beyond 20 minutes needed IVD injection at our emergency room. Sedation occurred in 17% of patients, which was attributed to IVD in 8% and SRT in 9% of patients. No respiratory depression was attributable to IVD or SRT. There was no significant statistical difference in efficacy and safety between these two forms of diazepam. Conclusion: Rectal diazepam solution, administered by capable caregivers, is as effective and safe as rectal administration of IVD for children with intractable epilepsy.